Pembinaan Akhlakul Karimah melalui Pembiasaan dan Keteladanan di SMP Ma’arif Grabag Kabupaten Magelang - Suryono, Suryono; Laili, Zuhrotul; Nursikin, Mukh (Lembaga Yasin AlSys, 2022)
Habituation and example in education are need because psychologically students tend to imitate an idolized figure, including the teacher. This research is a qualitative research with a case study at Ma’arif Grabag Districts Magelang Junior High School. The data collected was obtained from observations, documentation and interviews. Data analysis was carried out by reviewing all data, reducing, compiling, categorizing, checking the validity of the data, and drawing conclusions. The conclusion shows; The implementation of moral development at Ma’arif Grabag Districts Magelang Junior High School which is applied in routine programs thet are a must for students, forms of exemplary and habituation exemplified by teachers include discipline, the habit of greeting teachers of friends when meeting, reading Asma’ul Husna, tadarus Al-Qur’an, dhuha prayer in congregation,tausiyah, praying before and afterlessons, muhadara, flag ceremony, clean living, and religious activities; Moral development materials include religion and discipline, evaluation of coaching activities is carried out regularly once a month and reported to the Principal; Supporting factors include the participation of all school members, participation of parents, and students; The inhibiting factors include the interaction of students outside class hours with the outside environment which is sometimes not good, supervision is still lacking in habituation activities, and the use of information technology such as mobile phones is not controlled.